(untitled) (Scientific journal of the Fergana State University, 2026)
This article describes the results of the conference held by the Bukhara Society for the Protection of Historical and Cultural Monuments in the 80s of the last century, as well as the decisions and tasks they adopted. Over the course of three years, the work done by the company is analyzed, the successes and shortcomings achieved are discussed. The article highlights the events held by the society, the work done and the issues of paternity of historical monuments.